The Millet of the Matter: Archeobotanical Evidence for Farming Strategies of Western Han Dynasty Core Area Inhabitants - Liao, Jingwen; Li, Ming; Allen, Edward; Luo, Wuhong; Sheng, Pengfei (Frontiers in Plant Science, 2022)
Despite decades of investigation, consensus has yet to be reached on when and where wheat replaced millet as the primary crop in the core regions of early Imperial China. Previous studies have suggested that wheat cultivation likely became widespread prior to or during the Han Dynasty (202 BC-AD 220). Here, we tested this hypothesis by applying archaeobotanical tools to plant remains found in five pottery model granaries (cang) entombed in a newly excavated late Western Han burial at the Longzaocun cemetery in the Guanzhong Basin. This analysis allowed us to explore the extent of wheat expansion and agricultural strategies in the heartland of early dynastic China. Macro- and micro-botanical evidence shows that the Longzaocun residents consumed two kinds of crops: foxtail and common millet. Combining these findings with previous studies, we argue that millet-based multi-crop farming dominated the regional agricultural system during the Western Han Dynasty (202 BC-AD 8) and analyze the political and cultural motivations for the Han people’s usage on millet crops from the burial concepts and fiscal systems. Echoing previous studies, we argue that millets remained the most valuable subsistence food for inhabitants of the Loess Basins in the Han core, and that wheat was not cultivated on a large scale in this area during the Western Han Dynasty.